PERAN GERAKAN JAMA’AH DAN DAKWAH JAMA’AH DALAM INTERNALISASI NILAI-NILAI ISLAM DI RANTING MUHAMMADIYAH BLIMBINGREJO - Toni Ardi Rafsanjani; Muhammad Abdur Rozaq (Profetika: Jurnal Studi Islam, 2022)
The researcher aims to analyze and describe the role of the congregation movement and da'wah ja'ah in the internalization of Islamic values in Blimbingrejo. This research is qualitative research, the data collection uses observation and interviews. Data analysis was carried out using descriptive data analysis techniques which included three concurrent activities, data reduction, and presentation of conclusion drawing data. The results of this study are 1) the role of the congregation movement and congregational da'wah organized by the Muhammadiyah branch of Blimbingrejo; 2) the process of internalizing religious values to the branch congregation; 3) Doctrine of religious values strengthened by the word of Allah SWT and the hadith of the Prophet. The form of success is the growth of stronger religious understanding, changes in behavior in accordance with religious values, strong ukhuwah Islamiyah and progressive thinking. The process of internalizing religious values is conveyed during recitations and other religious activities. PRM Blimbingrejo continues to develop its da'wah methodology in fostering the congregation and developing Islam in the village.Peneliti bertujuan untuk menganalisis dan mendiskripsikan peran gerakan jama’ah dan dakwah ja’ah dalam internalisasi nilai-nilai keislaman di Blimbingrejo. Penelitian ini adalah penelitian kualitatif, pengumpulan datanya adalah observasi dan interview. Analisis data dialakukan dengan Teknik analisis data diskriptif yang mencakup tiga kegiatan bersamaan, reduksi data, penyajian data penarikan kesimpulan. Hasil penelitian ini adalah 1) peran gerakan jama’ah dan dakwah jama’ah yang diselenggarakan Pimpinan ranting Muhammadiyah  Blimbingrejo;  2) proses internalisasi nilai-nilai agama kepada jama’ah ranting; 3) Dotkrinasi nilai-nilai agama yang dikuatkan dengan firman Allah SWT dan hadist Nabi. Wujud keberhasilanya adalah pertumbuhan pemahaman agama semakin kuat, perubahan perilaku sesuai dengan nilai-nilai agama, ukhuwah Islamiyah yang kuat dan berfikir berkemajuan. Proses internalisasi nilai-nilai agama ini disampaikan pada saat pengajian dan kegiatan keagaam yang lain. PRM Blimbingrejo terus mengembangkan metodologi dakwahnya dalam membina jama’ah dan mengembangkan Islam di desa tersebut.